PENERAPAN REWARD DAN PUNISHMENT PADA MATA PELAJARAN FIKIH DI MIN 2 AGAM - Rani Permata Sari; Junaidi Junaidi; Salmi Wati; Arifmiboy Arifmiboy (KOLONI, 2022)
This research is motivated by the problems that occur at MIN 2 Agam, that fiqh teacher is less than optimal in the learning process and in the application of reward and punishment, teacher only give occasional reward and inconsistent in his application and the application of punishment is rarely applied, teacher often ignore students who commit violations, as a result most of the students are less enthusiastic in learning fiqh and lack achievement, and often violate the rules set by the teacher, this can be seen from observations when the fiqh teacher teach in class VB. Therefore, the researcher wants to know how to apply rewards for students who are diligent, enthusiastic and good during the learning process and want to know how to apply punishment to students who are lazy and like to break the rules from the teacher. The purpose of the application of reward and punishment is the students are motivated and enthusiastic in learning. This type of research is a field research with a descriptive qualitative method that describes the application of reward and punishment in fiqh subjects at MIN 2 Agam. In collecting data the researcher used observation and interview techniques. The main sources of data and informants in this study was fiqh teacher and supporting of informants, several students of class VB at MIN 2 Agam. Meanwhile, to analyze it, the researcher used steps of data reduction, data presentation and drawing conclusions. The results of the study are that at Madrasah Ibtidaiyah Negeri (MIN) 2 Agam, every teacher has the right to apply rewards and punishments to students where the rewards are aimed at the good of the students and to raise students' enthusiasm for learning so that students can be happy and more active in learning, as well as punishment that is imposed on them. implemented does not contain physical violence and violates the law but the punishment applied is educational and able to make students better for the future. Rewards and punishments applied by teachers also take various forms, there are rewards in the form of praise, additional values, prizes and punishments in the form of preventive and repressive ones. this way and it has been able to bring students in a more positive direction. Keywords: Reward, Punishment, Fiqh Subjects